Electricity pinch analysis method for flexibility supply-demand matching in power systems - Yaling Mao; Tiejiang Yuan; Xueqin Tian; Yue Teng (Energy Conversion and Management: X)
The growing integration of renewable energy into modern power systems presents significant challenges in maintaining flexibility supply–demand balance. Traditional operation simulation-based planning approaches often fail to provide effective flexibility matching mechanisms, resulting in either insufficient resource allocation or over-provisioning, while struggling to reconcile reliability requirements with computational complexity. Leveraging the theoretical framework of pinch technology from process engineering, this paper proposes an Electricity Pinch Analysis (EPA) method for flexibility assessment. First, the net-load profile is decomposed by successive variational mode decomposition (SVMD) optimized with the Red-billed Blue Magpie Optimization (RBMO) algorithm to construct a flexibility demand model. Subsequently, a unified characterization method is developed to model the amplitude-frequency characteristics of flexibility resources, ensuring compatibility with pinch analysis requirements. Guided by the supply–demand matching principles inherent to pinch analysis, a graphical method is introduced that efficiently aligns flexibility resources with demand. Source and sink composite curves are constructed and horizontally shifted to locate the pinch point, thereby identifying the bottleneck in flexibility balance. Finally, chronological operation simulations are carried out within the frequency band indicated by the pinch point to validate the feasibility of the planning outcome. By relying directly on frequency-domain characteristic parameters for resource planning, the proposed approach markedly reduces dependence on high-precision sequential forecasts and significantly mitigates the impact of power-prediction uncertainty on planning results.